2022
DOI: 10.1161/circgen.122.003712
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Polygenic Risk Scores for Coronary Heart Disease in a Middle Eastern Cohort Using Whole Genome Sequencing

Abstract: Background: Enthusiasm for using polygenic risk scores (PRSs) in clinical practice is tempered by concerns about their portability to diverse ancestry groups, thus motivating genome-wide association studies in non-European ancestry cohorts. Methods: We conducted a genome-wide association studies for coronary heart disease in a Middle Eastern cohort using whole genome sequencing and assessed the performance of 6 existing PRSs developed with methods such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…It will be important to validate them in an independent Middle Eastern cohort with welldefined cases and controls and to develop ancestry-specific PRSs. Recently, several PRSs for coronary heart disease were validated in a Middle Eastern cohort [31]. To improve equitable genetic risk prediction for diverse populations, collecting more well-defined and large disease cohorts are needed.…”
Section: Discussionmentioning
confidence: 99%
“…It will be important to validate them in an independent Middle Eastern cohort with welldefined cases and controls and to develop ancestry-specific PRSs. Recently, several PRSs for coronary heart disease were validated in a Middle Eastern cohort [31]. To improve equitable genetic risk prediction for diverse populations, collecting more well-defined and large disease cohorts are needed.…”
Section: Discussionmentioning
confidence: 99%
“…PGS development for predicting LDL-C levels or CVD within the wider Middle Eastern region based on local genomic variation has not been systematically explored. A recent study on a cohort of coronary heart disease (CHD) from Qatar showed that performance of PGS derived from European studies of CVD was comparable to the performance reported in Europeans (21).…”
Section: Introductionmentioning
confidence: 94%
“…Readers can then decide where they fall on the spectrum for each step based on unique aspects of their population and datasets available at their disposal. For example, in the case of an indigenous Arab population, where datasets are limited but environmental risk factors are unique, it might be necessary to borrow effect estimates from global GWAS studies (Saad et al., 2022). In South Asian or East Asian populations where there are emerging larger datasets, using population‐specific GWAS to update effect size estimates might be feasible (Koyama et al., 2020; Weissbrod et al., 2022).…”
Section: Multistep Approach To Optimize Prs For a Population Of Interestmentioning
confidence: 99%